Fotografia e(m) movimento: poéticas da locomoção na fixidez da imagem - Luis Moraes Coelho (2012)
By combining the terms photography and motion, within its wide range of hues, we aim to investigate and understand the context of poetic images resulting from experimental production processes. We start with the examination of its characteristics that constitute conventional assumptions, such as the properties contained in the fixity of the image in relation to moving bodies, the characteristics that link visual signs to the perception of reality through a linear flow of time, and the automatic ability of operating the apparatus in accordance with these assumptions. Then, outlined a historical scenario with apparatuses and factors involved in imaging techniques, relating them to their insertion in the history of art, specifically highlighting artists and photographers who brought the issue of moving to the center of their research, to be able to investigate and demonstrate structural differences. These differences are found both from an operational standpoint as from philosophical, as well, revealed between conventional photography and experimentalism, to the point of subverting much of its assumptions. We also seek to present and comment on works of contemporary poetics whose approach is based on the shown issues between photography and motion, in an attempt to delineate whether there is a relationship with the historical production.